2021
DOI: 10.5671/ca.45.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Practical Pedagogical Training During the Epidemic Through the Eyes of the Slovenian Physical Education Student Teachers

Abstract: In 2020, physical education teacher education (PETE) students of the Faculty of Sport of the University of Ljubljana (N = 46) had to complete a large part of the practical pedagogical training online. Using an online questionnaire, we investigated how they delivered distance learning in physical education (PE) at Primary Schools, the extent to which they achieved their objectives, encouraged students to move, delivered content, and assessed. The delivery mostly depended on whether the school included PE in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 3 On average, both PE teachers and students completing their practical pedagogical training, reported that most PE lessons took the form of independent student activity following written or recorded instructions, and the rest took the form of online outdoor or indoor live classes. 23 Between the infrastructure laws which remain unchanged, and the concerted efforts of PE teachers nationwide to deliver quality PE instruction remotely, the (A) ranking was retained for this indicator in both epochs.…”
Section: Resultsmentioning
confidence: 99%
“… 3 On average, both PE teachers and students completing their practical pedagogical training, reported that most PE lessons took the form of independent student activity following written or recorded instructions, and the rest took the form of online outdoor or indoor live classes. 23 Between the infrastructure laws which remain unchanged, and the concerted efforts of PE teachers nationwide to deliver quality PE instruction remotely, the (A) ranking was retained for this indicator in both epochs.…”
Section: Resultsmentioning
confidence: 99%
“…After another rock climb, the athlete' s reserves of energy substances can be well replenished. 13 The following day, serum CK and BU were significantly increased. Urine-specific gravity was more extraordinary than 1.030, and the positive detection rate of urine protein was over 80%.…”
Section: Body Composition and Muscle Coordinationmentioning
confidence: 93%